Real-time web-based microclimate monitoring of broiler chicken trucks on different shifts - Aérica C. Nazareno; Iran J. O. da Silva; Eduardo F. Nunes; Osvaldo Gogliano Sobrinho; Renata M. Marè; Carlos E. Cugnasca (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This research aimed to monitor and evaluate air-conditioned trucks transporting day-old chicks, in various shifts of travel, through general packet radio service (GPRS) technology to provide real-time thermal control for poultry industry managers. The Control-Broilers equipment used were GS-105 and the Monitorar Platform. GS-105 is composed of sensors, a microprocessor, GPRS, and batteries. The Monitorar Platform provided nine applications that acted in coordination with web technology RESTful services. Twenty-eight chick transports were evaluated and monitored using the Control-Broilers. Truck routes were supervised by two researchers to ensure real-time data transmission through laptops and smartphones. Three air-conditioned trucks were used during two of days shifts. The vehicles had the same dimensions, but the routes, travel times, and load densities varied. Measurements of the air temperature, relative humidity, and specific enthalpy inside the trucks were recorded every minute. The experimental design was entirely randomized in a 3 × 2 factorial scheme, which represented the three trucks (CL, CA and JA) in two transport shifts (day and night), containing four repetitions (travel).The air-conditioned trucks transporting day-old chicks presented a 92.85% efficiency for real-time data transmission using GPRS technology. The trucks during the travel shifts did not provide thermal homogeneity in chick loads. The night shift presented worse thermal conditions.